Telegram Chatbot Implementation Using Rasa Framework to Recommend Tourism in Semarang City - Anam, Farid Asroful; Anwar, Sariyun Naja (Jurnal Ilmiah Komputasi, 2024)
In the context of the rapid development of tourism, especially in Semarang City which offers 1393 tourist attractions, the confusion of tourists in choosing a destination is a challenge. This research proposes the implementation of a chatbot on the Telegram platform as a solution to facilitate tourists in determining tourist destinations that match their preferences. The research method includes data collection, conversation model, system design and development, implementation, and testing. By involving representative respondents, the survey provides a holistic picture of their perceptions and assessments of various aspects, reflecting the level of satisfaction and providing valuable insights. The survey results provide the percentage of answers from the total respondents, strengthening the validity and reliability of the data. The implementation of the chatbot proved to significantly help travelers by cutting search time and providing a satisfying interactive experience. However, performance evaluation using the Classification Report showed results that require improvement. Therefore, the research emphasizes the need for improved Machine Learning and Deep Learning performance evaluation to ensure more optimal results on Classification Report in the future.